1986
DOI: 10.1154/s0376030800021133
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Affecting X-Ray Microfluorescence (XRMF) Analysis

Abstract: X-ray Microfluorescence (XRMF) analysis uses a finely collimated beam of X-rays to excite fluorescent radiation in a sample (Nichols & Ryon 1986). Characteristic fluorescent radiation emanating from the small interaction volume element is acquired using an energy dispersive detector placed in close proximity to the sample. The signal from the detector is processed using a computer-based multi-channel analyzer.XRMF imaging is accomplished by translating the sample through the small X-ray beam in a step or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Micro-X-ray fluorescence (MXRF) was first demonstrated in the 1980s (Nichols et al , 1987) and has been in use for ~25 years. In one of the first reported MXRF studies of actinide samples, Schoonover and Havrilla (1999) demonstrated the key benefits of MXRF (and micro-infrared) in determining elemental heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-X-ray fluorescence (MXRF) was first demonstrated in the 1980s (Nichols et al , 1987) and has been in use for ~25 years. In one of the first reported MXRF studies of actinide samples, Schoonover and Havrilla (1999) demonstrated the key benefits of MXRF (and micro-infrared) in determining elemental heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…XRF is classically performed with a large area beam (millimeters to centimeters) as a bulk analysis technique. The emergence of capillary X-ray optics, which focus X-ray beams by multiple reflections off the inner surface of a tapered glass capillary or cluster of capillaries, has enabled the production of an X-ray beam focused to a diameter of 100 μm or finer from a modest, laboratory-scale X-ray tube source (Gurker, 1986; Nichols et al, 1987; Carpenter, 1989). Such a beam diameter is useful for mapping on a large spatial scale where the basic pixel step is matched to the beam size (Boehme, 1987; Carpenter & Taylor, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…By moving the specimen surface relative to a stationary X-ray beam, a two-dimensional elemental distribution image is collected by monitoring variations in elemental X-ray intensity versus position. These intensity differences correspond to relative differences in the concentration of a given element dispersed across the specimen (Nichols et al , 1987).…”
Section: Introductionmentioning
confidence: 99%